Сутнісна характеристикаінтелектуального капіталу підприємства - Чернявська, Ю. Б. (Ways to Improve Construction Efficiency, 2014)
In article on the basis of the analysis of the existing definitions of the intellectual capital author's vision of this category moves. The intellectual capital of the enterprise is meant as set of knowledge, abilities. Skills, experience, creativity, organizational abilities, etc. of employees of the enterprise who are effectively used in the course of production and make profit, increases its competitiveness and increases the market value of the enterprise concerning its balance cost.